كاریگه‌ری ئاووهه‌واو ئاسوده‌یی مرۆڤ له‌سه‌ر ڕوداوه‌كانی هاتووچۆ له‌پارێزگای دهۆك - صدیق, پ.ی.د. ئاشتی سلام; ئیبراهیم, خوێندكاری ماسته‌ر: ئازاد نبی صۆفی (Sulaimani Journal for Humanities, 2023)
The aim of the study is to evaluate the climatic races such as temperature, humidity and wind speed on human comfort using both equations (Thom, Siple & Bassel) and determine the effect of comfort on traffic accidents in Duhok province, Although the study assumes that some climate species have a greater impact on human comfort when their averages are too high or too low, For this purpose, the researcher relied on descriptive and analytical methods and the use of Thom's equation, Sable and Basel equations using the climate data recorded in the province. The study also identified the most favorable months and the most unfavorable months for traffic, which can be seen as a strong point by the relevant parties, in order to take necessary actions to reduce traffic accidents.
Keywords: كلیلی ووشهكان پارێزگای دهۆك ئاووههوا ئاسودهیی مرۆڤ ڕووداوهكانی هاتووچۆ